Uma princesa sem seu diadema : identidade, intervenções urbanas e usos dos espaços em São João del-Rei (1893-1922) - Arthur Marinho Silva Vargas (2022)
The present work aims to analyze the discussions that started around urban interventions and the uses of spaces in São João del-Rei between 1893 and 1922. Using primarily periodicals, it seeks to apprehend, in the first place, the main problems identified in São João by the men of the press, in a context of loss of economic centrality in the regional scope and political lack of prestige. In these circumstances, urbanistic works and the normalization of the lives of the inhabitants –proscribing and prescribing the place of each one, according to a bourgeois ideology of valorization of work, even with vestigial patriarchal elements –, were listed as the most adequate responses to these questions, in a selective appropriation of models disseminated on a global scale. Such projects and actions were justified by the existence of a “Sanjoanense tradition”, in which the local past and progressive anxieties were not necessarily exclusive. In this way, we seek to see how this Sanjoanense identity was built and what discursive and ideological mechanisms were mobilized in order to give consistency to such projects, which in turn were claimed as necessary instruments for the conservation of existing images about the city and its inhabitants.